Tunnel diode integrated rectangular patch antenna for millimetre range - Srivastava S.; Vishvakarma B.R.; Ansari J.A. (My University, 2025)
Theoretical investigations conducted for the Ge tunnel diode integrated rectangular patch antenna reveals that such an antenna exhibits frequency tunability with bias voltage. The Ge tunnel diode loaded patch can be operated in the millimetre range (53.517-56.4615 GHz). The range of frequency obtainable for operation is 2944.5 MHz. The radiation pattern shows variation with the bias voltage, and radiated power beamwidth and directivity vary inversely with bias voltage. Thus, the Ge tunnel diode loaded patch can be used to achieve electronic tuning (BW = 5.355%) with the bias voltage.